Current Challenges and Achievements in Maternal Immunization Research - Munoz, Flor M. (Frontiers in Immunology, 2018)
Maternal immunization has the potential to significantly improve maternal and child health worldwide by reducing maternal and infant morbidity and mortality associated with disease caused by pathogens that are particularly relevant in the perinatal period and in early life, and for which no alternative effective preventive strategies exist. Research on all aspects related to vaccines for administration during pregnancy is ongoing with support of multiple stakeholders and global participation. Substantial progress has been made, and the availability of new vaccines licensed exclusively for use in pregnant women to protect their infants has become an achievable goal. This review provides an update of the current challenges and achievements in maternal immunization research, focusing on recent milestones that advance the field and the prospects to make maternal immunization a feasible and accessible strategy to improve global health.